A respectable spell : transformations of samba in Rio de Janeiro - Sandroni, Carlos, 1958- (Lemann center for Brazilian studies series, 2021)
"This book is primarily about the social history and musical changes of samba in Rio de Janeiro from 1917 to the early 1930s, looking chiefly at the era's commercial recordings. The year 1917 marks the first time that a popular song designated as "samba" became a widespread Carnival success in the city. In the early 1930s, a new style of samba became dominant, such that it is still today the genre's primary point of reference. The book proposes an analysis and interpretation of the differences in the musical styles, highlighting their rhythmic aspects. It also shows how these differences are linked to the way in which samba and sambistas are understood in Rio de Janeiro's society and culture during this period. The first part of the book, "From Lundu to Samba," deals with popular music genres created during the second half of the nineteenth century, such as lundu, Brazilian tango, and maxixe, whose musical characteristics came to be shared with old-style samba. The book's second part, "From One Samba to Another," deals with the emergence of samba in Rio de Janeiro as a commercial genre of popular music, and with the creation and success of the new style of samba, paying special attention to the trajectories of Ismael Silva and Noel Rosa, composers representative of this transition"--